ASSOCIATION BETWEEN PSYCHOSOCIAL FACTORS AND STAGES OF ACNE: A COMMUNITY BASED EPIDEMIOLOGICAL STUDY IN LAHORE, PAKISTAN - Zikria Saleem; Dr. Nosheen Mustafa; Zunaira Akbar; Sonia Imtiaz (International Journal of Pharmacy & Integrated Health Sciences)
Background: There is no published epidemiological study to assess the prevalence, risk factors and management of acne based on severity among youth of Pakistan which could be helpful in guiding clinical decisions. Objective: Thus, the study was aimed at finding an association of different psychosocial and physiological factors like emotional status, diet, and menstrual cycle affecting severity and duration of acne. Methods: In this cross sectional observational study with 1175 pupils, initially screened for acne, the data of only 510 pupils (43.4%) -categorized according to Lehmann grading scale- were collected from the University of the Punjab, Lahore and its beleaguered community. Results: Our data suggested that 32.74%, 47.45% and 19.80% participants were suffering from mild, moderate and severe acne, respectively. Stress (p=0.002), anger (p=0.000), smoking (p=0.003), overproduction of oil (p=0.028), protein supplement (p=0.05), intake of cheese (p=0.044) and duration of acne (p=0.000) were strongly associated with severity of acne. Among all, only 65.88% of patients were taking either oral (doxycycline) or topical (clindamycin gel) medications, while others failed to opt any treatment. Conclusion: Taken together, mild to moderate acne is common among pupils of Lahore. Therefore, it is inevitable that targeted educational modules should be designed for the youth affected by acne due to psychosocial and physiological reasons along with clinical and non-clinical management preferences